ANALISIS PERANCANGAN STRATEGI DENGAN MENGGUNAKAN MATRIK SWOT PADA MTs. NEGERI 7 MAJALENGKA - Dadang (MADINASIKA, 2020)
This research is motivated by the declining quality possessed by MTs 7 Majalengka, one of which is the decline in students who are accepted at the secondary education level which is supported by quite a favorite. Therefore, researchers learn how to improve the quality of education by planning strategies and policies made by MTs Negeri 7 Majalengka to maintain excellence and supportive names. This analysis uses analysis of strengths, opportunities, and threats which are strategic planning methods used to overcome strengths, weaknesses, opportunities, and threats in the school. This type of research is a qualitative study with one variable, this research is field research by raising data in the field about the things that will be discussed. The results of this study show that the strategy carried out by MTs Negeri 7 Majalengka is to focus on the Vision and Mission to be a superior, Islamic and quality madrasa. Academic and non-academic activities are carried out optimally to produce a quality generation. The program is made of superior classes (Excelent classes), then special classes and regular classes.